The Comorbidities Coma Scale (CoCoS): Psychometric Properties and Clinical Usefulness in Patients With Disorders of Consciousness - Pistoia, Francesca; Carolei, Antonio; Bodien, Yelena G.; Greenfield, Sheldon; Kaplan, Sherrie; Sacco, Simona; Pistarini, Caterina; Casalena, Alfonsina; De Tanti, Antonio; Cazzulani, Benedetta; Bellaviti, Gianluca; Sarà, Marco; et al. (Frontiers in Neurology, 2019)
Although comorbidities have a well-known impact on the functional recovery of patients with disorders of consciousness, including coma, vegetative state (VS) and minimally conscious state (MCS), a specific tool for their assessment in this challenging group of patients is lacking. For this aim, a multistep process was used to develop and validate the Comorbidities Coma Scale (CoCoS) in a sample of 162 patients with a diagnosis of coma, VS or MCS admitted to four Acute Inpatient Rehabilitation Units. To establish the psychometric properties of the scale, content validity and internal consistency were investigated through Exploratory Factor Analysis in the whole sample (n=162). Interrater reliability, assessed by the weighted Cohen’s kappa (Kw), and concurrent validity of the scale as compared to the Greenfield Scale, assessed by ρ Spearman’s correlation coefficient, were investigated in a subsample of patients (n=52) within two of the above units. Our findings provided evidence of a good content validity of the scale, with the identification of a 12-factor structure representing the different comorbid dimensions of the target population. Inter-rater reliability was excellent in both the rehabilitation units where the assessment was made [Kw 0.98 (95% CI 0.96-0.99)]. CoCoS total scores correlated significantly with total scores of the Greenfield Scale (ρ=0.932, 95% CI 0.89-0.96; P<0.0001) indicating that CoCoS has concurrent validity while being more informative about the specific pattern of comorbidities of these challenging patients. The CoCos is a new tool which standardizes the approach to assessment of comorbid conditions and reliably identifies the category and severity of each comorbidity detected. It may be used for both clinical and research applications.